2011
DOI: 10.1590/s0103-21002011000200020
|View full text |Cite
|
Sign up to set email alerts
|

Terapias não farmacológicas no alívio da dor neuropática diabética: uma revisão bibliográfica

Abstract: Painful diabetic neuropathy is characterized by intense pain. The objective was to conduct a literature review regarding the pharmacologic therapies used to relieve that pain. A literature search was conducted of six (6) data sources, in the last 12 years (1998 to 2010) using the keywords: diabetes, diabetes, painful neuropathy, neuropathic pain, treatment, and other similar terms. Thirteen articles were selected that addressed the use of acupuncture, reiki, photic stimulation, electromagnetic stimulation of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
1
2
0
2
Order By: Relevance
“…A similar result was observed in South Africa 24 , where "burning" (36.5%) was the most reported complaint, followed by "pricking and tugging" (35.4%) and "numbness" (31.2%). These results are in agreement with the literature, pointing tingling, numbness, burning, continuous, lacerate pain with needle stick sensation as clinical manifestations of the NP 2,47 . In terms of intensity of pain, it was observed that 36.36% of the volunteers reported severe pain according to the VAS, while people with pain with non-neuropathic characteristics, only 13.04%.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…A similar result was observed in South Africa 24 , where "burning" (36.5%) was the most reported complaint, followed by "pricking and tugging" (35.4%) and "numbness" (31.2%). These results are in agreement with the literature, pointing tingling, numbness, burning, continuous, lacerate pain with needle stick sensation as clinical manifestations of the NP 2,47 . In terms of intensity of pain, it was observed that 36.36% of the volunteers reported severe pain according to the VAS, while people with pain with non-neuropathic characteristics, only 13.04%.…”
Section: Discussionsupporting
confidence: 93%
“…However, when asked about following a pain treatment, 52.27% of the people with neuropathic pain reported having some type of intervention, while within people with non-neuropathic pain it was only 26.09%, showing association (0,0400). It is believed that this difference among the groups may have occurred due to the extremely unpleasant characteristics of the NP, frequently reported by the patients 2 , that makes them seek treatment. Likewise, a study showed that the group of patients with diabetic neuropathy and NP was more medicated in comparison with the group with neuropathy, but without pain 33 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dessa forma, a acupuntura se mostra como uma ótima opção terapêutica não farmacológica no tratamento da dor neuropática, sobretudo, em pacientes que sofrem com os variados efeitos adversos das medicações habituais para o alívio da dor (FRANCO et al, 2011). A eficácia da técnica no modelo da dor neuropática pode ser compreendida pela ação local e sistêmica de substâncias que têm seu estímulo dado pela ativação de acupontos, bem como pelo estímulo natural ao aumento da circulação local.…”
Section: Benefício Da Acupuntura No Tratamento Da Dor Neuro-páticaunclassified
“…Após a leitura dos artigos inclusos no estudo, elaborou-se um quadro apresentando informações básicas dos artigos, tais como: autores, idioma, periódico, ano de publicação e tipo de estudo. grande potencial terapêutico, uma vez que os seus benefícios sobrepujam as contraindicações.Com base nisto, estudo de revisão realizado porFranco et al (2011) demonstrou que esta modalidade de tratamento não farmacológico é uma excelente abordagem terapêutica aos pacientes com neuropatias diabéticas em membros inferiores.Outras modalidades de laserterapia de baixa intensidade referida nos achados bibliográficos desta revisão abordam que a laser acupuntura também é efetiva como terapêutica deste tipo de acometimento.De acordo com os resultados desse estudo foi possível observar que à aplicação da terapia com fotobiomodulação mostra-se efetiva no tratamento em pacientes com neuropatias diabéticas em membros inferiores, além disso possibilitou a identificação dos benefícios desta modalidade terapêutica, dentre elas o baixo potencial de reações adversas e o limitado número de contraindicações.Apesar da utilização de padrões diversos na aplicação do uso do laser, os estudos analisados confirmaram os benefícios desta técnica não invasiva, tornando-a uma excelente indicação não farmacológica para pacientes com este tipo de acometimento.…”
unclassified